The music of the text in Villa Amalia by Pascal Quignard - El Fahmy, Nabila (Romanica Olomucensia, 2022)
Music is a predominant theme that permeates all the works of Pascal Quignard. In fact, it transforms his texts into veritable melodic scores. His novel Villa Amalia reads like a polyphonic piano that is in tune with the main character, Ann, to the point where the strings of the instrument merge with those of the character's soul. The study of this work aims at analysing the Quignardian text through the prism of a musical aesthetic, as a poetic place that exploits all the resources of resonance that the experience of writing offers. To approach this novel, therefore, a sound analysis of the text has been opted for, adopting a semiotic-poetic approach that attempts to bring out the musicality of the text and its polyphonic composition. This will allow the unbreakable link between the letter, the note, the body, and the instrument in the novelistic universe of Pascal Quignard to be shown. Although it is focuses on one of his works, his other writings will also be cited in order to identify the fundamental aspects of his thought. This paper is by no means exhaustive, but it allows for a better understanding of the musical approach employed by the author in his quest for scriptural sonority.
Keywords: Pascal Quignard; Villa Amalia; music; scriptural musicality; polyphony